Discussion of Vertical Information Transfers: The Association between Retailers' Sales Announcements and Suppliers' Security Returns - Bernard, Victor L. (Journal of Accounting Research, 1985)
Information environment, Supply chain Information, Sales announcements, Supplier-Customer relation